Life Cycle Assessment (LCA) of Environmental and Energy Systems - Passarini, Fabrizio; Ciacci, Luca (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
The transition towards renewable energy sources and "green" technologies for energy generation and storage is expected to mitigate the climate emergency in the coming years. However, in many cases, this progress has been hampered by our dependency on critical materials or other resources that are often processed at high environmental burdens. Yet, many studies have shown that environmental and energy issues are strictly interconnected and require a comprehensive understanding of resource management strategies and their implications. Life cycle assessment (LCA) is among the most inclusive analytical techniques to analyze sustainability benefits and trade-offs within complex systems and, in this Special Issue, it is applied to assess the mutual influences of environmental and energy dimensions. The selection of original articles, reviews, and case studies addressed covers some of the main driving applications for energy requirements and greenhouse gas emissions, including power generation, bioenergy, biorefinery, building, and transportation. An insightful perspective on the current topics and technologies, and emerging research needs, is provided. Alone or in combination with integrative methodologies, LCA can be of pivotal importance and constitute the scientific foundation on which a full system understanding can be reached.